# |
ODE |
Mathematica |
Maple |
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}3 y \left (t^{2}+y\right )+t \left (t^{2}+6 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {2 y}{x}-3
\] |
✓ |
✓ |
|
\[
{}y \cos \left (t \right )+\left (2 y+\sin \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{x}+\cos \left (y\right )+\left (\ln \left (x \right )-x \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x^{2}-1\right ) \left (x^{3}-3 x \right )^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x^{2}\right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{\sqrt {x^{2}-16}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-2 x -10}{\left (x +2\right ) \left (x -4\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x^{2}+x}{\left (1+x \right ) \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {x^{2}-16}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (-x^{2}+4\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}-16}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right ) \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )^{3} \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-12 t y^{\prime }+42 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 x^{3}-x +2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (2 t \right )-\cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (\frac {1}{x}\right )}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\ln \left (x \right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x -4\right ) y^{3}}{x^{3} \left (y-2\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime }+24 y^{\prime }+153 y = 0
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 4 y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )-2 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}4 x \left (x^{2}+y^{2}\right )-5 y+4 y \left (x^{2}+y^{2}-5 x \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \sin \left (x \right )^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+\frac {25 y^{\prime \prime }}{2}-5 y^{\prime }+\frac {629 y}{16} = 0
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 4 y \left (t \right ), y^{\prime }\left (t \right ) = -4 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = -5 x \left (t \right )+4 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+2 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+45 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+12 y = 2
\] |
✓ |
✓ |
|
\[
{}2 x -3 y+\left (2 y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (x y\right )+\sin \left (x \right )+x \cos \left (x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x^{2}-x +1}{\left (x -1\right ) \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{\sqrt {x^{2}-1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = t
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 x -9}{3 \left (x -3\right )^{{2}/{3}}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+t^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+t^{2} = \frac {1}{y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y+\frac {1}{1-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{5}}
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{t} = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 t^{2}-t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sqrt {t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {25-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {25-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {25-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {25-y^{2}}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = t^{3}
\] |
✓ |
✓ |
|
\[
{}t^{3} y^{\prime }+t^{4} y = 2 t^{3}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+t y = \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \sec \left (t \right ) = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{t -3} = \frac {1}{t -1}
\] |
✓ |
✓ |
|
\[
{}\left (t -2\right ) y^{\prime }+\left (t^{2}-4\right ) y = \frac {1}{2+t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {-t^{2}+4}} = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {-t^{2}+4}} = t
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = t \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (t \right ) = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {t}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}\frac {1}{2 \sqrt {t}}+y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}6+4 t^{3}+\left (5+\frac {9}{y^{8}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {6}{t^{9}}-\frac {6}{t^{3}}+t^{7}+\left (9+\frac {1}{s^{2}}-4 s^{8}\right ) s^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 \sinh \left (4 y\right ) y^{\prime } = 6 \cosh \left (3 x \right )
\] |
✓ |
✓ |
|